Manual therapy and segmental stabilization in the treatment of cervical radiculopathy - Rafael Souza Aquaroli; Elder Soares Camacho; Luis Marchi; Luiz Pimenta
Abstract Introduction: Cervical radiculopathy (CR) is one of the diseases that most affect the cervical spine, causing radicular symptoms in the ipsilateral limb. Conservative treatment aim recover of both mechanical and physiological functions through neural mobilization techniques, along with the activation of the deep neck flexors with cervical segmental stabilization, combining techniques of joint mobilization and manipulation, which seeks mobility improvement of crucial areas of the cervical spine. The objective of this study was to evaluate a multimodal treatment to enhance the outcomes of conservative care in patients diagnosed with CR. Methods: The sample consisted of 11 patients with CR, between 21 and 59 years old, 3 female and 8 male. It was recorded the Visual Analogue Scale (VAS) for pain, the Functional Development of the Neck Pain and Disability Scale (NPDS) and the goniometry during shoulder abduction. The intervention plan was composed by neural mobilization, intermittent cervical traction, pompages, stretching, myofascial inhibition techniques, manipulative techniques and cervical segmental stabilization exercises. After 12 weeks of treatment, subjects underwent a new evaluation process. Results: Before the treatment, subjects reported an average pain of 7 (± 1.48) in VAS, whose dropped to average 1.18 (± 1.99) (p < 0.01). Functional disability evaluated in NPDS was 36 (± 10.95) before treatment decreasing to 11.45 (± 9.8) (p < 0.01) after the treatment. Range of motion of the ipsilateral upper limb was restores by increasing from 9.2° (± 8.2) to 137° (± 24.4) (p < 0.01). Conclusion: The proposed treatment approach was effective, significantly improving the results of analgesia and functional disability a series of cases of patients diagnosed with cervical radiculopathy. {#}